Charter of the City of Dallas, § 84, DALLAS, CHARTER OF THE CITY (John F. Worley 1899). - (:unkn) unknown (My University, 1899)
The city council shall have full power and authority by ordinance to regulate, control and prohibit the carrying of firearms and other weapons within the city limits, and is hereby empowered to provide and inflict the same punishment therefor as is now or hereafter may be provided by the State law against persons unlawfully carrying weapons."
Keywords: CARRY